Persepsi Siswa Teknik Komputer Jaringan Terhadap Pembelajaran Berbasis Learning Management System (LMS) Dalam Meningkatkan Motivasi Belajar Di SMK Negeri 1 Kota Serang - Falih Ihza; Dewi Surani; Siti Aminah (Cakrawala Pedagogik, 2023)
The development of technology that exists today has been applied in various dimensions of life, including education, the increasingly widespread use of learning media that uses technology makes it easier for teachers to provide material anywhere and anytime. This technology-based learning media facilitates the learning process in terms of effectiveness & efficiency. The study aims to determine the views or perspectives of student learning motivation in using the Learning Management System (LMS) as a learning media. This type of research was conducted using descriptive quantitative research. This research data collection uses a survey method with observation techniques, interviews and online questionnaires or questionnaires via google form. Based on the results of observations supported by interviews and on the analysis of questionnaire data obtained from 100 students of the Network Computer Engineering expertise program in the 2022/2023 school year at SMK Negeri 1 Serang City, it shows that students have a positive perception of the utilization of learning management system-based learning so as to increase learning motivation, supported by the results of learning motivation scoring criteria with a final result of 3.48 which states that "agree" Learning Management System learning media can increase motivation and encouragement in student learning motivation in certain conditions and situations.